Studying The Language Style in Advertising Slogans for Food and Beverages Aired on Indosiar and ANTV TV Channels - Syamsuddin, Syamsuddin; Faradillah, Yenny (Yayasan Kyadiren, 2022)
The objective of this study is to examine the language style and semantic meanings of food and beverage advertising slogans on television. The research approach utilized is descriptive qualitative, utilizing recording and note-taking techniques. The study concentrates on the language style used in food and beverage advertising slogans on Indosiar and ANTV television stations from January to June 2022. The findings of the research reveal that the language style used in food and beverage advertising on television is quite diverse, with hyperbolic language being the dominant style. The preparation of advertising slogans employs a variety of language styles with the intention of influencing and attracting consumers to purchase the promoted product.